Ethics of an International Political Relation: Serbia and the European Union - Radojičić, Mirjana S. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
The subject of this paper is the relation between Serbia and the European Union viewed from an international ethic perspective. The author tries to point to the continuity of the Euro-American policy, directed with interests and not with values towards this former Yugoslav republic and its majority nation. The central topic of this paper is the stand taken by the European Union towards the complex and decades-long Kosmet issue. The author is trying to prove that the issue, such as it is, represents a continuity of an inconsistent attitude of most European states towards the Serbian state territorial issue, which attitude has been persisting for two decades. The stand taken by the author is that by acquiescing to the formation and stabilization of a newly-created state in the Serbian territory, the European Union has actually assumed the role of a medium of overseas attempts at attaining as painlessly as possible the goal of the secession of Kosovo, which territory has been proclaimed of special American national interest and hence, of a legitimate influence. In the conclusion of this paper, the author points to possible consequences that the method of resolving this important state territorial issue could have on the stability of the Western Balkans in near or remote future.
Keywords: international politics; international ethics; Serbia; Kosovo and Metohija; European Union